2016
DOI: 10.1111/ced.12812
|View full text |Cite
|
Sign up to set email alerts
|

Male genital lichen sclerosus in recipients of bone marrow transplants

Abstract: We describe two patients who received haematopoietic stem cell marrow transplantation, and developed male genital lichen sclerosus (MGLSc), one of whom also had squamous carcinoma in situ (Bowen disease). MGLSc has previously been associated with graft-versus-host disease. Various aetiological factors for LSc have been proposed, including a role for chronic occluded epithelial exposure to urine. A number of factors imply that the risk of malignant transformation in this bone marrow transplant group is likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In the past 10 years, several case reports [15][16][17][18][19][20][21][22][23][24] and a few cohort studies [25][26][27][28] have specifically reported on manifestations of genital male chronic GvHD (cGvHD), often associated with systemic cGvHD. The incidence of genital cGvHD in men varies between 5% 26 and 20% 25,27 , depending upon the evaluated cohort (i.e., asymptomatic patients vs patients who seek care for symptoms).…”
Section: Genital Chronic Gvhdmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past 10 years, several case reports [15][16][17][18][19][20][21][22][23][24] and a few cohort studies [25][26][27][28] have specifically reported on manifestations of genital male chronic GvHD (cGvHD), often associated with systemic cGvHD. The incidence of genital cGvHD in men varies between 5% 26 and 20% 25,27 , depending upon the evaluated cohort (i.e., asymptomatic patients vs patients who seek care for symptoms).…”
Section: Genital Chronic Gvhdmentioning
confidence: 99%
“…125,140 Single cases of squamous cell carcinoma have been reported in patients with genital lichen sclerosis, likely related to cGvHD. 23 Penile carcinoma might be underestimated, since carcinogenesis in male genital lichen sclerosis in the general population can be as high as 10%. 141…”
Section: Male-specific Cancersmentioning
confidence: 99%